Advanced algorithms for early detection of first damage during static tensile tests (Fracture and Structural Integrity, 2025)
The Static Thermographic Method (STM) involves analyzing the thermal behavior of a specimen subjected to a quasi-static tensile test. The temperature trend, measured by an infrared camera, follows three phases where the first and second are cooling phases, while the third a heating phase. A limit stress value can be determined, corresponding to the macroscopic stress level at the point of slope change between the first and second phase, indicating the occurrence of initial damage. The onset of plasticity is the reason of fatigue failure; thus, the limit stress can be adopted as a first indication of failure stress level for design purposes. This work aims to objectify the Static Thermographic Method, which currently relies on the operator's experience and skill in identifying the different thermal phases during the static tensile test. Three different algorithms have been developed to determine the best mathematical model for the temperature trend over time, eliminating the subjectivity of data observation.
Keywords: Infrared Thermography; Risitano Thermographic Method; Static Thermographic Method; Damage; Fatigue